1999
DOI: 10.1046/j.1440-1827.1999.00818.x
|View full text |Cite
|
Sign up to set email alerts
|

Composite renal cell carcinoma and angiomyolipoma: A study of the histogenetic relationship of the two lesions

Abstract: The purpose of the present study was to investigate the possible histogenetic relationship of renal cell carcinoma (RCC) and angiomyolipoma (AMYL) occurring in the same renal nodule by examining two cases of composite RCC and AMYL in patients without stigmata of tuberous sclerosis and by reviewing the medical literature of similar cases. Case 1 represents an epithelioid variant of AMYL with multiple additional nodules of typical AMYL in a surgically removed kidney. The patient subsequently developed a lesion c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…Unlike typical AMYL, which has a benign clinical course, epithelioid AMYL is often associated with an unfavorable evolution, including recurrence of the lesion in the retroperitoneum and liver and eventual death. 2,3 We report a case of recurrent epithelioid AMYL diagnosed by fine needle aspiration biopsy (FNAB) and describe the cytologic appearance of the lesion, with an emphasis on immunocytochemical studies for differentiation of this lesion from epithelial neoplasms of the kidney.…”
Section: Background: Epithelioid Angiomyolipoma (Amyl) Is a Variant Omentioning
confidence: 99%
“…Unlike typical AMYL, which has a benign clinical course, epithelioid AMYL is often associated with an unfavorable evolution, including recurrence of the lesion in the retroperitoneum and liver and eventual death. 2,3 We report a case of recurrent epithelioid AMYL diagnosed by fine needle aspiration biopsy (FNAB) and describe the cytologic appearance of the lesion, with an emphasis on immunocytochemical studies for differentiation of this lesion from epithelial neoplasms of the kidney.…”
Section: Background: Epithelioid Angiomyolipoma (Amyl) Is a Variant Omentioning
confidence: 99%
“…Mai et al . reported the possible origination of RCC from AML, 12 but Cheng et al . concluded that AML and RCC were coincidentally present at the same location 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Concomitant renal cell carcinoma was observed in 26% of patients with angiomyolipoma and tuberous sclerosis, while 2–7% of patients with pure renal angiomyolipoma had evidence of renal cell carcinoma. 4,21–26 …”
Section: Discussionmentioning
confidence: 99%
“…Concomitant renal cell carcinoma was observed in 26% of patients with angiomyolipoma and tuberous sclerosis, while 2-7% of patients with pure renal angiomyolipoma had evidence of renal cell carcinoma. 4,[21][22][23][24][25][26] Nodal angiomyolipoma associated with renal angiomyolipoma was not described again until 1965 and 40 more cases have been described since then. 1,4,5,[9][10][11][12][13] The actual incidence of nodal involvement with angiomyolipoma is unknown and may never be assessed because fewer radical nephrectomies will be performed for angiomyolipoma.…”
Section: Discussionmentioning
confidence: 99%